Biosynthesis, Characterization and Evaluation of Biological Properties of Biogenic Gold Nanoparticles Synthesized Using Nothapodytes foetida Leaf Extract - Datkhile, Kailas D.; Durgavale, Pratik P.; Patil, Madhavi N.; Jagdale, Nilam J.; Deshmukh, Vinit N. (Nanoscience & Nanotechnology-Asia, 2021)
Background and Objective: Biogenic nanomaterials are recently being researched in biomedicine for their antioxidant, antimicrobial, anti-inflammatory and antitumor performance. In this study, gold nanoparticles (AuNPs) were biologically synthesized using Nothapodytes foetida (N. foetida), a camptothecin producing plant, to evaluate its potent cytotoxic activity against cancer cells and antimicrobial activities against human pathogenic bacteria. Methods: The AuNPs were characterized by UV-visible spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and dynamic light scattering (DLS). The antimicrobial activity of AuNPs was determined by conducting the minimum inhibitory concentration (MIC) assay on gram positive and gram negative bacteria, whereas cytotoxicity against cancer cells was assessed through the MTT assay and genotoxicity was assayed by DNA fragmentation. Results: TEM and DLS results showed the synthesis of 20-200 nm sized M. foetida AuNPs (NFAuNPs). The NFAuNPs exerted growth inhibitory effects on gram negative bacteria with the MIC for the inhibition of Eschericia coli, Pseudomonas aeruginosa being 0.15 mg/mL and 0.25 mg/mL respectively. The cytotoxicity results indicated that the sublethal concentrations of NFAuNPs for inhibiting 50% of cell growth (IC50) of cancer cells including HeLa, MCF-7 and HCT-15 after 48 h of exposure were 7.2, 9.67 and 5.28 μg/mL respectively. DNA fragmentation in cells exposed to 10-75 μg/mL of NFAuNP concentrations revealed their genotoxic effects. Conclusion: The study revealed the biogenic synthesis of AuNPs using the N. foetida plant extract and its biological potential as an antimicrobial and anticancer agent.
Keywords: Notaphodytes foetida